A visual rhetorical analysis of Queer visibility strategies active in contemporary American television - Daniels, Madison (The Motley Undergraduate Journal, 2023)
Research on queer visibility in media has frequently focused on the content of queer representation (Dhaenens & Bauwel, 2012; Manuel, 2009; McCarthy, 2001). This study challenges this approach by analyzing the strategies of how queer visibility is conveyed in contemporary American television dramas. The analysis focuses on scenes with implicit and explicit queer references from the shows Station 19 and Mr. Robot. Through a visual rhetorical analysis of visual and verbal performance of queerness, this study found four major strategies of queer visibility, which will be discussed in my presentation. Firstly, there is a strategy of heterosexual characterization, meaning queerness is permitted if it has heterosexual attributes, one of the queer persons being masculine and the other feminine. Secondly is the Greek strategy, a historical strategy inspired by ancient Greek times when the significant age gap between two men in a queer relationship was acceptable. Thirdly is the semi-explicit strategy, where the expression of queerness in a relationship is mixed between overtones and undertones of queerness. Finally, there is the implicit strategy where queerness between two characters only exists in the undertones, gestures, and words. These findings highlight the repertoire of queer visibility strategies possibly present in other American television shows.